FMRI for vegetative and minimally conscious states. (28th November 2012) - Turner-Stokes, Lynne; Kitzinger, Jenny; Gill-Thwaites, Helen; Playford, E Diane; Wade, Derick; Allanson, Judith; Pickard, John
Abstract : A more balanced perspective